Franco and Hitler : Spain, Germany, and World War II - Payne, Stanley G. (New Haven : Yale University Press, 2008)
"Was Franco sympathetic to Nazi Germany? Why didn't Spain enter World War II? In what ways did Spain collaborate with the Third Reich? To what extent did Spain assist Jewish refugees? This is the first book in any language to answer these intriguing questions. Stanley Payne, a leading historian of modern Spain, explores the full range of Franco's relationship with Hitler, from 1936 to the Fall of the Reich in 1945. Whereas Payne investigates the evolving relationship of the two regimes up to the conclusion of World War II, his principal concern is the enigma of Spain's unique position during the war, as a semi-fascist country struggling to maintain a tortured neutrality. Why Spain did not enter the war as a German ally, joining Hitler to seize Gibraltar and close the Mediterranean to the British navy, is at the center of Payne's narrative. Franco's only personal meeting with Hitler, in 1940 to discuss precisely this, is recounted here in groundbreaking detail that also sheds significant new light on the Spanish government's vacillating policy toward Jewish refugees, on the Holocaust, and on Spain's German connection throughout the duration of the war."--Provided by publisher
I: From Civil War to World War -- The Spanish Civil War -- Hitler's strategy in the Civil War -- Military and international significance of the Civil War -- A tilted neutrality -- II: "Nonbelligerence" -- Franco's temptation -- The meeting at Hendaye and its aftermath -- The Zenith of collaboration -- Temptation continues -- The Blue division -- Temptation abates -- Temptation ends -- III: The struggle to escape the "axis stigma" -- Spanish diplomacy and the7 Holocaust (I) -- Spanish diplomacy and the Holocaust (II) -- Neutrality by compulsion -- The end of the relationship.
Includes bibliographical references (pages 277-308) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
In English.
Keywords: Hitler, Adolf, -- 1889-1945.; Franco, Francisco, -- 1892-1975.; World War, 1939-1945 -- Diplomatic history; World War, 1939-1945 -- Spain; Spain -- Politics and government -- 1939-1975.; Spain -- Foreign relations -- Germany; Germany -- Foreign relations -- Spain; Guerre mondiale, 1939-1945 -- Histoire diplomatique; Guerre mondiale, 1939-1945 -- Espagne; Espagne -- Politique et gouvernement -- 1939-1975.; Espagne -- Relations extérieures -- Allemagne; Allemagne -- Relations extérieures -- Espagne; HISTORY -- General; Diplomatic history; Diplomatic relations; Politics and government; Germany; Spain; Außenpolitik; Deutschland; Spanien; Tweede Wereldoorlog; Spanje; Duitsland; World War, 1939-1945 -- Diplomatic history; World War, 1939-1945 -- Spain; Spain -- Politics and government -- 1939-1945.; Spain -- Foreign relations -- Germany; Germany -- Foreign relations -- Spain; 1939-1975